(Table 1) Porosity measurements, median pore diameter of pore sizes and volume fractions of bulk sediment from different Holes of IODP site 333 - Daigle, Hugh (Supplement to: Daigle, H (2014): Microporosity development in shallow marine sediments from the Nankai Trough. Marine Geology, 357, 293-303, https://doi.org/10.1016/j.margeo.2014.09.041, 2015)
Microporosity by performing low pressure nitrogen adsorption measurements on 13 shallow marine mudstone samples from the Nankai Trough offshore Japan. The samples were from two reference Sites on the incoming Philippine Sea Plate, and one Site above the accretionary prism. I determined pore size distributions using the Barrett–Joyner–Hallenda (BJH) model, and merged these with existing mercury injection capillary pressure (MICP) measurements to construct a full distribution covering micro- to macropores. I found that overall pore sizes decrease with consolidation, and that microporosity content (pores < 2 nm in diameter) is influenced mainly by mineralogy, with some influence of diagenetic processes. A small amount of microporosity (~ 0.25% of bulk sediment volume) is present in these sediments at the time of burial, presumably contained mainly in clays. Additional microporosity may develop as a result of alteration of volcanic ash at the reference Sites, and may be related to diagenetic processes that create zones of anomalous high porosity. Comparisons with porewater chemistry (K+, Ca2 +, Sr, Si) show inconsistent relationships with microporosity development and cannot confirm or deny the role of ash alteration in this process. The strongest correlation observed at the three Sites was between microporosity volume and clay mineral fraction. This suggests that microporosity content is determined mainly by detrital clay abundance and development of clay as an ash alteration product, with some contribution from amorphous silica cement precipitated in the zones of anomalous high porosity.